2018
DOI: 10.1111/papt.12193
|View full text |Cite
|
Sign up to set email alerts
|

The link between self‐compassion and psychotic‐like experiences: A matter of distress?

Abstract: Low levels of self-compassion are associated with being more distressed by psychotic experiences. As the self-compassion facets isolation and overidentification are most strongly related to distress, prevention and intervention programmes may benefit from focusing on these negative facets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 75 publications
1
4
1
Order By: Relevance
“…It is not simply the case that participants lacked the self-compassion necessary to gain the benefits described in the literature; the positive aspects of self-compassion were negatively correlated with the negative aspects of self-compassion and both forms of self-criticism in our sample. As such, our findings did not necessarily align with those of Scheunemann et al (2019), who found a significant correlational relationship between self-compassion and PLEs. This is particularly interesting given that existing research often frames self-compassion as a resilience factor for self-criticism (Mavituna et al, 2022).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…It is not simply the case that participants lacked the self-compassion necessary to gain the benefits described in the literature; the positive aspects of self-compassion were negatively correlated with the negative aspects of self-compassion and both forms of self-criticism in our sample. As such, our findings did not necessarily align with those of Scheunemann et al (2019), who found a significant correlational relationship between self-compassion and PLEs. This is particularly interesting given that existing research often frames self-compassion as a resilience factor for self-criticism (Mavituna et al, 2022).…”
Section: Discussioncontrasting
confidence: 99%
“…For example, CFT is premised on the idea of switching between basic evolved systems, namely engagement of the caring/attachment system and downregulation of the threat system (Gilbert, 2009; Gumley et al, 2010), with evidence that self‐compassion and self‐criticism activate distinct neural systems (Doerig et al, 2014; Kim et al, 2020; Longe et al, 2010). Perhaps self‐compassion is simply not associated with PLE presence in subclinical populations, despite seemingly being efficacious in reducing symptom distress and frequency in both clinical and subclinical populations (Bourgin et al, 2020; Karcher et al, 2020; Kelleher et al, 2014; Mavituna et al, 2022; Scheunemann et al, 2019). In line with this, our findings suggest that self‐compassion and self‐criticism are separate factors with different relationships to PLEs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower‐self compassion was linked to more severe paranoia, positive symptoms of psychosis and distress linked to psychotic symptoms in both groups. This aligns with previous research showing that self‐compassion is associated with positive and negative symptoms of psychosis (Collett et al, 2016; Mavituna et al, 2022; Scheunemann et al, 2019). However, self‐compassion did not differ between clinical and non‐clinical groups, which is at odds with Collett et al (2016) who found lower levels of self‐compassion in people with persecutory delusions compared to a healthy control group which was matched by age and gender.…”
Section: Discussionsupporting
confidence: 92%
“…In psychosis, a recent meta-analysis found that self-compassion is related to positive and negative symptoms, emotional distress and cognitive disorganization (Mavituna et al, 2022). People with persecutory delusions also score significantly lower on self-compassion than non-clinical controls (Collett et al, 2016), and self-compassion predicts distress related to delusional beliefs in the non-clinical population (Scheunemann et al, 2019).…”
Section: Practitioner Pointsmentioning
confidence: 99%